A major plan practice report in Mead Johnson Nutritionals at 2309 Don Chino Roces Ave., Extension, Makati City, Philippines - Condeza, Lesele Osip (2006)
The plant practice at the Mead Johnson Nutritionals, located at 2309 Don Chino Roces Avenue, Extension, Makati City, Philippines, which is a division of Bristol-Myers Squibb (Phil.), Inc. engaged the student to activities involved in powdered milk production. This sets a venue for the applications of the theories and principles she learned while taking up food technology degree program. The whole duration of the plant practice was divided to allow the student to meander to the different department involved in the manufacturing of powdered milk. The student was exposed to quality assurance, receiving and dispensing of raw materials, quality control and to the production itself. Information regarding the company was gathered and some problems were identified. After which recommendations were raised. The total hours of plant practice was accomplished with in 30 days